Phytochemical Screening and In Vitro Evaluation of the Antioxidant Potential of Dichloromethane Extracts of Strychnos henningsii Gilg. and Ficus sycomorus L. - Kenedy Wanjala Wafula; Joseph Kiambi Mworia; Mathew Piero Ngugi (The Scientific World Journal)
Medicinal plants are a rich source of antioxidants such as flavonoids, phenols, tannins, and alkaloids among others and are currently used as alternative and complementary drugs in the management of stress-related disorders. Strychnos henningsii and Ficus sycomorus have been traditionally used by the people of Mbeere, Embu county, Kenya, as medicine for the treatment of various oxidative stress-related disorders such as diabetes and rheumatism; however, no empirical data are available to authenticate the said claim. The aim of this study was to evaluate preliminary phytochemical screening and in vitro antioxidant activity of dichloromethane (DCM) leaf extract of S. henningsii and stem bark extract of F. sycomorus using DPPH, hydrogen peroxide, and ferric reducing power assays; total flavonoids and phenolic compounds were also determined by colorimetric assay and Folin–Ciocalteu reaction, respectively. Phytochemical screening showed that both extracts possessed saponins, flavonoids, phenols, steroids, alkaloids, and cardiac glycosides; however, terpenoids were found to be absent in S. henningsii. The total phenolic and flavonoid content of the DCM stem bark extract of F. sycomorus was lower than that of the leaf extract of S. henningsii. These extracts significantly exhibited strong antioxidant activities at different concentrations tested. The IC50 values of S. henningsii and F. sycomorus were 0.325 mg/ml and 0.330 mg/ml for hydrogen peroxide and 0.068 mg/ml and 0.062 mg/ml for DPPH, respectively. Both DCM leaf and stem bark extracts of S. henningsii and F. sycomorus were found to have strong ferric reducing power. Therefore, both extracts showed significant nonenzyme-based antioxidant activities. The two plants possess phytochemicals that have significant antioxidant properties.